Forensic psychiatry influences of evil - Mason, Tom (Humana Press)
Many conscientious mental health professionals caring for disturbed patients have either unscientifically formulated for themselves notions of "evil" to explain the behavior of their patients, or have been given patients described by judges and the press as "evil." Although such notions may be deemed unscientific, beyond the purview of medicine, and better suited for discussion by theologians and moral philosophers, the fact remains that these notions of "evil" have a definite impact on the practice of psychiatry, if not all medical fields. In Forensic Psychiatry: Influences of Evil, Tom Mason brings together an international panel of experts from diverse specialties to examine the idea of "evil" in a medical context, specifically a mental health setting, to consider how the concept can be usefully interpreted, and to elucidate its relationship to forensic psychiatry. The authors challenge the belief that the concept of "evil" plays no role in "scientific" psychiatry and is not helpful to our understanding of aberrant human thinking and behavior. Among the viewpoints up for debate are a consideration of organizations as evil structures, the "medicalization" of evil, destruction as a constructive choice, violence as a secular evil, talking about evil when it is not supposed to exist, and the influence of evil on forensic clinical practice. Among the highlights are a psychological exploration of the notion of "evil" and a variety of interesting research methods used to explore the nature of "evil." Illuminating and provocative, Forensic Psychiatry: Influences of Evil offers mental health professionals a challenging survey of how the concept of "evil" can be understood from a variety of viewpoints and integrated into forensic psychiatry. Organizations as evil structures - The psychopharmaceutical complex - Intention, excuse, and insanity - An archaeology of the psychopath - The comforts of evil - Madness, badness, and evil - Destruction as a constructive choice - Violence as secular evil - Scapegoat, spectacle, and confessional - The vilification of victimized children in historical perspective - Evil - Capacities and dispositions - Should radical evil be forgiven? - Mad, bad, and evil - Talking about evil, even when it is not supposed to exist - The influence of evil on forensic clinical practice - Hope in the face of evil.